A small-scale robotic manipulandum for motor control study with rodents. (18th July 2021) - Inoue, Takahisa; Terada, Shin; Matsuzaki, Masanori; Izawa, Jun
Abstract : Computational models of motor learning have been examined experimentally with human participants using a robotic manipulandum that produces force perturbations on their reach trajectories. Here, we developed a small-scale robotic manipulandum for rodent studies. This device enabled us to conduct the same motor control experiments typically used for human study on rodents in order to examine the neural basis of the computational process of motor control and learning. We present the design of the manipulandum and controller system in addition to kinematic analysis of the link structures. We also confirmed the feasibility of the developed system for rodent studies. GRAPHICAL ABSTRACT: UF0001